Left ventricular remodeling and arterial remodeling in patients with chronic kidney disease stage 1–3. (9th August 2015) - Pluta, Agnieszka; Stróżecki, Paweł; Krintus, Magdalena; Odrowąż-Sypniewska, Grażyna; Manitius, Jacek
Abstract: Introduction : Chronic kidney disease (CKD) is an independent factor for cardiovascular system complications, such as arterial hypertension, left ventricular hypertrophy (LVH), heart failure or accelerated atherosclerosis progression. The aim of the paper was to analyze left ventricular and arterial remodeling in patients with CKD stages 1–3 to identify the subclinical marker of cardiovascular system damage which changes first in the course of CKD. Methods : The examined group consisted of 90 patients with CKD stage 1–3 and 30 subjects constituting the control group. Left ventricular mass index (LVMI), left ventricular relative wall thickness (RWT) and ejection fraction (EF) were determined by echocardiographic examination. Pulse wave velocity (PWV) between the carotid and femoral arteries as well as common carotid artery intima–media thickness (IMT) was measured. 24-h ambulatory blood pressure monitoring was performed in all subjects. Results : No differences were found between blood pressure values in the examined groups of patients with CKD1, CKD2 and CKD3. Concentric remodeling was found in 20.0%, concentric hypertrophy in 22.2% and eccentric hypertrophy in 18.9% of patients. LVMI values in patients with CKD2 and 3 were higher than in the control group. IMT values in patients with CKD3 were higher than in patients with CKD2. PWV in patients with stage 3 CKD was significantly higher than in the control group ( p < 0.05). Conclusions : In the course of CKD, the left ventricle undergoes remodeling earlier than large arterial vessels. Echocardiographic assessment of LVH in early stages of CKD may identify patients at increased cardiovascular risk.